Performing history : theatrical representations of the past in contemporary theatre - Rokem, Freddie, 1945- (Iowa City : University of Iowa Press, 2000)
In his examination of the ways in which theatre participates in the ongoing representations of and debates about the past, Freddie Rokem concentrates on the ways in which theatre after World War II has presented different aspects of the French Revolution and the Holocaust, showing us that by "performing history" actors bring the historical past and the theatrical present together.
Theatrical EnergiesTextual Energies; From Textual to Performative Energies; Performance Energies; The Eavesdropper and the Survivor-Witness; Metaphysical Energies; Epilogue; Notes; Bibliography; Index.
Includes bibliographical references (pages 217-236) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Historical drama -- 20th century -- History and criticism; Holocaust, Jewish (1939-1945), in literature; France -- History -- Revolution, 1789-1799 -- Literature and the revolution; Théâtre historique -- 20e siècle -- Histoire et critique; Holocauste, 1939-1945, dans la littérature.; France -- Histoire -- 1789-1799 (Révolution) -- Littérature et révolution.; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; PERFORMING ARTS -- Theater -- History & Criticism; Historical drama; Holocaust, Jewish (1939-1945) in literature; France; Drama; Französische Revolution; Historisches Drama; Judenvernichtung; Literatur; Europa; Toneelvoorstellingen; Motieven (kunst); Holocaust; Franse Revolutie; 1789-1999; Criticism, interpretation, etc; History